FINANCIAL MANAGEMENT STRATEGIES IN THE ERA OF DIGITAL TRANSFORMATION - Nursansiwi, Dwi Arini; Armiani, Armiani (Management Studies and Business Journal (PRODUCTIVITY), 2024)
Digital transformation (DT) has had a significant impact on financial management, but its specific influence on the cost of capital and corporate financing structures is still poorly understood. This research aims to identify how DT influences capital costs and changes in financing structures across industries. Using approach Systematic Literature Review (SLR) based on PRISMA guidelines, this research finds that DT can reduce the cost of capital through increased efficiency and transparency, as well as lead to a shift in financing preferences with the adoption of technologies such as fintech and blockchain. The implications of this research provide insight for financial managers, investors and policy makers to formulate strategies that support technology adoption in corporate financing.